Penciptaan Makhluk dalam Perspektif Hadis - Abdul Fatah; Badrudin Badrudin (Jurnal Budi Pekerti Agama Islam, 2025)
The This study examines the debate surrounding the first created being in Islamic cosmology, where various opinions exist. Some argue that the first creation was the Pen (al-Qalam), while others claim it was the Throne (‘Arsh), the air, or the Light of Muhammad (Nur Muhammad). The main issue addressed is the limited and fragmented information found in classical hadith sources regarding the sequence and nature of the initial creation. Methodologically, this research employs a qualitative approach by analyzing the chapter Bad’ al-Khalq (The Beginning of Creation) in key hadith collections. The findings show that although some hadiths mention early creations such as the characteristics of heaven and hell, the seven layers of the earth, and angels, detailed and systematic narratives about the order of the first created beings remain scarce. Various views on who or what was created first appear in the literature, ranging from al-Qalam and ‘Arsh to Nur Muhammad, but no absolute consensus has been reached. This study aims to fill that gap by compiling and analyzing relevant hadiths to provide a more focused and in-depth perspective on the first created being and the sequence of creation. Additionally, this research emphasizes the theological and cosmological significance of these beings and their implications for understanding the structure and purpose of the universe. It is hoped that the results of this study will enrich the body of Islamic scholarship and encourage deeper reflection on the orderliness and existence of Allah’s creation.